The Host Gaze in Global Tourism - Moufakkir, Omar (CABI, 2014)
This book is based on the notion that analy- sis similar to that of the tourist gaze (Urry, 1990, 2002) can be applied to the host gaze. We can use our understanding of the gaze to make sense of the wider society. In Urry’s words, to consider how host communities construct their gaze upon tourists is a ‘good way of getting at just what is happening in the “normal society”’ (Urry, 2002, p. 2). We gaze at what we encounter, and this gaze is socially and culturally organized (Foucault, [1963] 1973). The concept of Foucault’s medical gaze can help us to grasp tiny anomalies in our globalized world. For the purpose of this book, the gaze of the medic can help us to gaze systematically upon the gazes of the host. The host gaze involves looking at the host–guest encounter with interest and curiosity. There is the gaze of the gazer and the gaze of the gazee or the object of the initial gaze. Both gazes are sub- ject to change with changing economic, demographic, social, political, cultural and other societal phenomena (MacCannell, 2001; Urry, 2002). Just as the tourist gaze is dynamic (Urry, 2002), the host gaze is also changing, depending on who is the tourist and who is the host (Moufakkir, 2011). Just as there is no single tourist gaze, the host gaze must also vary by society, social group